Developing Countries, Dispute Settlement, and the Advisory Centre on WTO Law - Bown, Chad P.; McCulloch, Rachel (World Bank, Washington, DC, 2014)
Critical appraisals of the current and potential benefits from developing country engagement in the World Trade Organization (WTO) focus mainly on the Doha Round of negotiations. This paper examines developing country participation in the WTO dispute settlement system to enforce foreign market access rights already negotiated in earlier multilateral rounds. The dispute data from 1995 through 2008 reveal three notable trends: developing countries sustained rate of self-enforcement actions despite declining use of the Dispute Settlement Understanding (DSU) by developed countries, developing countries increased use of the DSU to self-enforce their access to the markets of developing as well as developed country markets, and the prevalence of disputes targeting highly observable causes of lost foreign market access, such as antidumping, countervailing duties, and safeguards. The paper also examines potential impacts of the Advisory Centre on WTO Law (ACWL) into the WTO system in 2001. A close look at the data reveals evidence on at least three channels through which the ACWL may be enhancing developing countries' ability to self-enforce foreign market access: increased initiation of sole-complainant cases, more extensive pursuit of the DSU legal process for any given case, and initiation of disputes over smaller values of lost trade.